Cognitive biases and heuristics in terms of behavioral economics: Applications of anchoring effect and loss aversion - Sevgin, Mehmet (My University, 2019)
The assumptions of standard economics describes humans as a selfish, rational and insensitive species. According to this view, since humans are extremely rational about their choices, they do not mix their feelings with their choices. However, since real-world observations and controlled experiments contradict rationality, we must doubt the assumptions of standard economics. It was believed that people are perfectly rational in their choices and economic decisions for many years. However, in real life, there are many mistakes and irrationality examples that are done by individuals according to experimental evidences. Therefore, behavioral economists accept the rationality but do not accept the perfect rationality. Hence, they renamed this term as ''bounded rationality''. The main purpose of this study is analyzing human behaviors during their economic actions to have a better perspective about the economy and human life. In this study, first, I analyze the rationality principle in economics. Moreover, I discuss cognitive biases and heuristics during the decision-making process of individuals regarding experimental findings. In the last part, I analyze two experiments that I conducted with students at University of Wroclaw and Yıldız Technical University to test rationalities of individuals regarding some cognitive biases.

Standart iktisadi düşünce insanı bencil, rasyonel ve duygusuz bir varlık olarak tanımlar. İnsanlar son derece rasyonel olduklarından kararlarına duygularını karıştırmazlar. İktisatta uzun süre insanların mükemmel derecede rasyonel olduğuna inanıldı. Ancak, gerçek hayattaki bazı gözlemler ve kontrollü deneyler rasyonalite ile çeliştiği için standart iktisadın varsayımlarına şüphe ile yaklaşmalıyız. Bu sebepten ötürü, davranışsal iktisatçılar rasyoneliteyi kabul ederler ancak tam rasyoneliteyi kabul etmezler. Bu yüzden bu kavramı ‘’sınırlı rasyonelite’’ olarak yeniden adlandırdılar. Bu çalışmanın temel amacı iktisat ve insan hayatı hakkında daha iyi bir perspektif kazanabilmek adına insanların iktisadi faaliyetleri sırasındaki davranışlarının rasyonelliğini analiz etmektir. Bu çalışmada ilk olarak iktisatta rasyonalite kavramını analiz ettim. Ayrıca gerçek hayatta insanların karar verme süreçlerinde yaptıkları bazı bilişsel yanlılıklar ve sezgileri deneysel gözlemler ışığında tartıştım. Son kısımda da insanların rasyonelliğini bazı bilişsel yanlılıklar açısından test etmek adına Polonya’da Wroclaw Üniversitesi’nde ve Türkiye’de Yıldız Teknik Üniversitesi’nde öğrencilerle yaptığım sınıf deneylerini analiz ettim.
Tez (Yüksek Lisans) - Yıldız Teknik Üniversitesi, Sosyal Bilimler Enstitüsü, 2019
Keywords: Davranışsal iktisat; Deneysel iktisat; Bilişsel yanlılıklar ve sezgiler; İktisatta rasyonalite; Behavioral economics; Experimental economics; Cognitive biases and heuristics; Rationality in economics